Isolamento de compostos bioativos das folhas de jambo (Syzygium malaccense) - Prasniewski, Anaclara (2019)
Jambo (Syzygium malaccense) is a medicinal plant used in Brazil for therapeutic purposes because it has hypoglycemic and anti-inflammatory potential. Despite its widespread use of traditional medicine, studies involving its leaves are still scarce. Thus, there is a lack of information about its chemical composition and biological activities. In this work, a study was carried out to isolate bioactive compounds from S. malaccense leaves, using bioguided monitoring by antioxidant activity assays such as: Iron reduction (FRAP), radical scavenging of synthetic (DPPH and ABTS) and peroxyl radical (ORAC) and content of total phenolic compounds (TPC). The chemical profile was determined by means of chromatographic techniques (HPLC-DAD-FL and UHPLC-ESI-Q-TOF-MS / MS). Initially, two exhaustive successive extractions (E1 and E2) were tested: E1 - made from the crude leaves and E2 starting from a crude extract EtOH: H2O (40:60 v/v), using the lyophilized material. Using the following solvents: Hexane, dichloromethane, ethyl acetate, acetone, ethanol and ethanol: water 40:60 v/v. After analyzing the chemical profile and antioxidant activity (AA), it was verified that the solvent of medium polarity (acetone) allowed a greater extraction of bioactive compounds. Thus, the acetone fraction (Fr-Ace) originated from extraction 2 (E2), was characterized by high levels of TPC and antioxidant activity. The compounds identified by CLAE-DAD-FL in this fraction were myricitrin (14.12 mg g-1), quercetin (0.88 mg g-1), catechin (0.84 mg g-1) and gallic acid (3.57 mg g-1). The results obtained for Fr-Ace from the UHPLC-MS/MS trial allowed the identification of 30 compounds, of which 25 are unprecedented for S. malaccense leaf extract, of the compounds belonging to the class of flavonoids. The purification of Fr-Ace on an open column allowed the collection of 96 subfractions, which after thin layer chromatography (TLC) analysis were reassembled in 19. The characterization of phenolic compounds from the 19 subfractions demonstrated that AA was potentiated after purification (HPLC-SEMIPREP) and 3 compounds were isolated. Compound 1 (C1) was identified by HPLC-DAD-FL as the flavonoid glycosylated myricitrin. Compounds 2 and 3 (C2 and C3) showed profiles in ultraviolet and medium infrared absorption assays that indicate similar behavior with the class of flavonoids. The isolated compounds showed high bioactivity against sequestration of the DPPH and superoxide radical and in reducing the Folin-ciocalteau and Fe3+ (FRAP) reagent. Techniques such as NMR (13C and 1H), and UHPLC-MS MS will still be applied for complete identification and confirmation of the compounds. However, this work demonstrated that the bioguided isolation and chemical characterization of S. malaccense allowed to prove the biological potential and its chemical composition, rich in glycosylated flavonoids, justifying its therapeutic use. From the results obtained it is possible to suggest the use of the leaves of jambo in new herbal formulations, as a substitute extract of synthetic antioxidants, and as a source of the compound myricitrin.